1984
DOI: 10.1152/ajprenal.1984.247.5.f863
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synthetic atrial natriuretic factor on renal function and renin release

Abstract: Studies were performed in anesthetized dogs (n = 5) to determine the effects of synthetic atrial natriuretic factor on renal function and renin release. Intrarenal infusion of synthetic atrial natriuretic factor (ANF) (0.3 microgram X kg-1 X min-1) resulted in a transient increase in renal blood flow (126 +/- 8 to 148 +/- 11 ml/min). The duration of this transient vasodilation was 3.1 +/- 0.4 min. Continued infusion was followed by a slight decrease in renal blood flow (126 +/- 8 to 117 +/- 8 ml/min) and an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
198
2
6

Year Published

1985
1985
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(225 citation statements)
references
References 15 publications
19
198
2
6
Order By: Relevance
“…CNP, given to anesthetized dogs had greater hemodynamic activity than ANP, but it was not natriuretic even when administered directly into the renal artery (46,48) . The observation of no change in sodium excretion is unique to this peptide when compared with ANP or BNP, which in previous studies produced marked natriuresis despite similar systemic hemodynamic changes (49). This is consistent with the report of Currie et al (49), who suggested that the renal hemodynamic and natriuretic actions of ANP are affected by the COON-terminal part of the peptide, which is absent in CNP.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…CNP, given to anesthetized dogs had greater hemodynamic activity than ANP, but it was not natriuretic even when administered directly into the renal artery (46,48) . The observation of no change in sodium excretion is unique to this peptide when compared with ANP or BNP, which in previous studies produced marked natriuresis despite similar systemic hemodynamic changes (49). This is consistent with the report of Currie et al (49), who suggested that the renal hemodynamic and natriuretic actions of ANP are affected by the COON-terminal part of the peptide, which is absent in CNP.…”
Section: Discussionsupporting
confidence: 88%
“…The observation of no change in sodium excretion is unique to this peptide when compared with ANP or BNP, which in previous studies produced marked natriuresis despite similar systemic hemodynamic changes (49). This is consistent with the report of Currie et al (49), who suggested that the renal hemodynamic and natriuretic actions of ANP are affected by the COON-terminal part of the peptide, which is absent in CNP. In contrast, in the presence of NEP inhibition, CNP has a natriuretic action in dogs, which is due to inhibition of distal sodium reabsorption without increasing urinary cGMP excretion (50).…”
Section: Discussionsupporting
confidence: 88%
“…The mode of action of ANF on kidney function is still debated [7]. The hormone appears to enhance directly the glomerular filtration rate and both sodium and water filtration fractions [ 15,161. An inhibitory effect on tubular reabsorption has also been proposed [ 16,171. Specific high-affinity receptor sites have been documented in aorta [18], adrenal cortex [19], posterior lobe of the pituitary gland [14] and in kidney cortex [ 181.…”
Section: Introductionmentioning
confidence: 99%
“…Burnett et al 1984Burnett et al , 1986Maack et al 1984; Wakitani et al 1985; Kleinert et al 1986). But the mechanism by which atrial extract or atrial natriuretic peptide produces a natriuresis and diuresis is still unclear.…”
mentioning
confidence: 99%